A Brief Review on Cerium Oxide (CeO2NPs)-Based Scaffolds: Recent Advances in Wound Healing Applications - Allu I.; Kumar Sahi A.; Kumari P.; Sakhile K.; Sionkowska A.; Gundu S. (My University, 2025)
The process of wound healing is complex and involves the interaction of multiple cells, each with a distinct role in the inflammatory, proliferative, and remodeling phases. Chronic, nonhealing wounds may result from reduced fibroblast proliferation, angiogenesis, and cellular immunity, often associated with diabetes, hypertension, vascular deficits, immunological inadequacies, and chronic renal disease. Various strategies and methodologies have been explored to develop nanomaterials for wound-healing treatment. Several nanoparticles such as gold, silver, cerium oxide and zinc possess antibacterial properties, stability, and a high surface area that promotes efficient wound healing. In this review article, we investigate the effectiveness of cerium oxide nanoparticles (CeO2NPs) in wound healing—particularly the effects of reducing inflammation, enhancing hemostasis and proliferation, and scavenging reactive oxygen species. The mechanism enables CeO2NPs to reduce inflammation, modulate the immunological system, and promote angiogenesis and tissue regeneration. In addition, we investigate the efficacy of cerium oxide-based scaffolds in various wound-healing applications for creating a favorable wound-healing environment. Cerium oxide nanoparticles (CeO2NPs) exhibit antioxidant, anti-inflammatory, and regenerative characteristics, enabling them to be ideal wound healing material. Investigations have shown that CeO2NPs can stimulate wound closure, tissue regeneration, and scar reduction. CeO2NPs may also reduce bacterial infections and boost wound-site immunity. However, additional study is needed to determine the safety and efficacy of CeO2NPs in wound healing and their long-term impacts on human health and the environment. The review reveals that CeO2NPs have promising wound-healing properties, but further study is needed to understand their mechanisms of action and ensure their safety and efficacy. © 2023 by the authors.